Model Optimization of Shale Gas Reservoir Volume Fracturing Dissolved Gas Simulation Adsorbed Gas - Hao Dong; Yi Zhang; Zongwu Li; Chao Jiang; Jiaze Li; Tao Wu; Liting Wang; Chuangjiang Wang; Hao Wang; Fujing Li; Qian Ru (Geofluids)
Shale reservoirs have some natural fractures with a certain density and connectivity. The basic percolation model of shale gas reservoir: the black oil model of gas-water phase is used as the basic model, and the dissolved gas is used to simulate adsorbed gas. Accurate description of natural fractures: random distributed discrete fracture model is used as the basic model to describe natural fractures. By comparing the calculation results of single medium (including random distributed discrete fracture model) and double medium model, the model for predicting shale gas productivity is optimized.